A marginal analysis framework to incorporate the externality effect of ordering perishables. (2022) - Sasanuma, Katsunobu; Delasay, Mohammad; Pitocco, Christine; Scheller-Wolf, Alan; Sexton, Thomas
Abstract: The exact analysis of optimal ordering policies for periodic-review perishable inventory systems is challenging because of their high-dimensional state space arising from multiple interrelated ordering decisions over many periods and age distributions of on-hand products. We develop a new marginal analysis framework to approximate this complex multiple-decision model into a single-decision model with an externality term, which internalizes the long-term impact of ordering decisions. Our externality-based approximation utilizes a constant base-stock policy; it is fast and easy to apply. Numerical experiments show that our approach provides state-dependent ordering amounts almost identical to the optimal dynamic programming-based policy.